An unexpected version of horror autotoxicus: anaphylactic shock to a self-peptide - Pedotti, Rosetta; Mitchell, Dennis; Wedemeyer, Jochen; Karpuj, Marcela; Chabas, Dorothée; Hattab, Eyas M.; Tsai, Mindy; Galli, Stephen J.; Steinman, Lawrence (Nature immunology, 2001)
EAE can refer either to experimental autoimmune encephalomyelitis or experimental allergic encephalomyelitis. Although EAE is classically a prototypic T helper 1 (T H 1) cell–mediated autoimmune disease, it can also be induced by T H 2 cells. Characteristically, the most severe manifestation of allergy, anaphylaxis, is associated with exposure to a foreign antigen that is often derived from medication, insect venom or food. We report here that, after self-tolerance to myelin is destroyed, anaphylaxis may be triggered by a self-antigen, in this case a myelin peptide. “Horror autotoxicus”, which was initially described by Ehrlich, may not only include autoimmunity to self, it may also encompass immediate hypersensitivity to self, which leads to shock and rapid death.